Paediatric non‐Hodgkin lymphoma ‐ perspectives in translational biology. (24th March 2016) - Shiramizu, Bruce; Mussolin, Lara; Woessmann, Wilhelm; Klapper, Wolfram
Summary: Exciting advances have been achieved for infants, children and adolescents diagnosed with, and treated for, non‐Hodgkin lymphoma (NHL). In spite of these successes, new frontiers are being paved to improve the prognosis for those who relapse or have resistant disease. This review summarizes some of the novel approaches and ideas in NHL monitoring, diagnosis and treatment as discussed at the 5th International Symposium on Childhood, Adolescent and Young Adult Non‐Hodgkin Lymphoma on October 22nd–24th 2015 in Varese, Italy.